Cyclic utilization method of maleic anhydride epoxidation catalyst
By using specific anionic resin adsorption and automatic analysis catalysts, the problem of high catalyst desorption and recycling costs in epoxy succinic acid production is solved, and the efficient recycling of the catalyst and the improvement of product quality is achieved.
Patent Information
- Application Number
- CN202411812973.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing epoxy succinic acid production technology, the catalyst tungstate or molybdate is prone to desorption during recycling, affecting product quality, and traditional recycling methods consume high energy and cost.
Specific anionic resins are used to adsorb the catalyst in the reaction system, and the catalyst is automatically analyzed under the reaction temperature and pH conditions, avoiding alkaline washing and desorption processes, and multiple recycling of catalysts and resins are realized.
It realizes efficient recycling of catalysts, reduces production costs and energy consumption, avoids catalyst residues in the product, and ensures the low metal content of the product.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fine chemical production, and particularly relates to a recycling method for a maleic anhydride epoxidation catalyst. Background Art
[0002] Epoxysuccinic acid is produced by maleic anhydride catalyzed epoxidation. It is a phosphorus-free and nitrogen-free chemical raw material, which can be used as a cross-linking agent, surfactant and plasticizer. As a raw material, polyepoxysuccinic acid (PESA) produced by ring-opening polymerization of epoxysuccinic acid is a phosphorus-free and nitrogen-free and biodegradable scale inhibitor with excellent performance. It has replaced many traditional phosphorus-containing water treatment agents and is an important water treatment agent product.
[0003] At present, the production technology of epoxy succinic acid is relatively mature, and most of them use maleic anhydride as raw material, which is first hydrolyzed, and then synthesized by hydrogen peroxide epoxidation under the action of a catalyst. The catalyst mainly uses one or more of tungstate, vanadate and molybdate. For example, patent CN1286797C discloses a method of synthesizing epoxy succinic acid by epoxidation of maleic anhydride using sodium tungstate / ammonium vanadate or sodium tungstate / ammonium molybdate as a composite catalyst; patent US4654159 uses maleic anhydride as raw material, first alkaline hydrolysis, and then sodium tungstate as a catalyst, and epoxidation reaction with hydrogen peroxide to generate epoxy succinate; patents CN1470493A and CN101602852B also mention the use of sodium tungstate or sodium molybdate as a catalyst in the synthesis of polyepoxy succinic acid to epoxidize maleic acid into epoxy succinic acid.
[0004] In actual production, the epoxidation process of maleic acid and hydrogen peroxide is highly exothermic and easily generates tartaric acid as a byproduct. In the water system, tungstate or molybdate will mix with tartaric acid and epoxysuccinic acid and is difficult to separate. The metal ions tungsten or molybdenum will affect the product quality, so there are many studies trying to recycle tungsten and molybdenum catalysts for reuse.
[0005] For example, patents CN103755945B and CN103709387B respectively introduce methods for preparing solid catalysts using sodium tungstate supported by styrene macroporous resin to synthesize epoxy succinic acid or polyepoxy succinic acid. The preparation steps of this supported catalyst are complicated, and the catalytic efficiency of sodium tungstate is low. After repeated use, tungstate ions will desorb, which will increase the content of metal tungsten in the product system and affect the product quality.
[0006] Patent CN211586523U proposes to use anionic resin to adsorb and desorb tungstate or molybdate catalysts in the system to achieve catalyst recycling. However, in the alkaline solution desorption process, the amount of alkali and water is large, and the subsequent catalyst concentration and extraction consumes a lot of energy, which increases production costs.
[0007] Patent CN112517032B discloses a composite carrier heteropoly acid catalyst, which is made by using a carrier such as silicon dioxide to load tungstate or molybdate, which is convenient for the recovery of the catalyst after cyclization, and the content of metal tungsten and molybdenum in the system after the reaction is ≤20ppm. However, with the repeated use of the composite carrier heteropoly acid catalyst, metal ions such as tungsten and molybdenum will slowly desorb from the carrier under high temperature, resulting in excessive content of metal tungsten and molybdenum in the product system, which will also affect product quality.
[0008] At the same time, the applicant has found in the research that the supported catalyst obtained by loading the catalyst tungstate or molybdate using silica as a carrier will slowly desorb the catalyst as the reaction time progresses in the synthesis reaction of epoxysuccinic acid, resulting in the supported catalyst being relatively stable in the initial few cycles of use, and the subsequent catalyst will gradually desorb from the carrier, which not only affects the catalytic efficiency but also causes product pollution.
[0009] In summary, how to ensure the catalytic efficiency of the catalyst while leaving no catalyst residue in the final product system and ensuring the low metal content of the product is an urgent problem to be solved in the current epoxysuccinic acid production technology. To this end, the present invention provides the following technical solutions. Summary of the invention
[0010] In view of the above problems, the present invention provides a method for recycling maleic anhydride epoxidation catalyst. By designing reaction parameters and steps, the tungsten- and molybdenum-containing catalyst is recycled in the maleic anhydride epoxidation reaction system, thereby saving the catalyst dosage.
[0011] To achieve the above object, the technical solution adopted by the present invention is: The recycling method of the maleic anhydride epoxidation catalyst of the present invention, 1) Maleic anhydride and water are put into a reaction kettle, and a sodium hydroxide aqueous solution is added dropwise for hydrolysis reaction to obtain a maleic acid aqueous solution, and then sodium tungstate or sodium molybdate is added as a catalyst, and a hydrogen peroxide aqueous solution is added dropwise to react to obtain an epoxysuccinic acid reaction solution; 2) The temperature of the synthesized epoxysuccinic acid reaction liquid is lowered to 20-30°C, and all of it is passed into an anion exchange column, and the anion of the catalyst is adsorbed by the anion exchange resin. Then, the anion exchange column is eluted with pure water of 1-2 times the mass of the anion exchange resin. The eluent and the adsorbed reaction liquid are used for the synthesis of polyepoxysuccinic acid. After elution, the anion exchange column is disassembled, and the anion resin inside is taken out for standby use; 3) Add a certain amount of maleic anhydride and water to the reactor, then drop 32% by mass of liquid alkali for hydrolysis, stop dropping the liquid alkali when the pH value of the system reaches 5-6, add the anion resin adsorbed with the catalyst in step 2) to the reactor, raise the temperature to 55-65°C, start dropping a certain amount of 25% by mass of hydrogen peroxide aqueous solution, and complete the addition in 2-3 hours. Continue to keep the temperature for 1-2 hours and then cool down. After the temperature of the reaction liquid drops to 20-30°C, filter and separate the anion resin and the epoxysuccinic acid reaction liquid. The obtained anion resin and the epoxysuccinic acid reaction liquid are treated according to the operation described in step 2 to complete the recycling of the catalyst.
[0012] According to the recycling method of maleic anhydride epoxidation catalyst, in step 1), maleic anhydride and water of equal mass are put into a kettle, and a 32% by mass sodium hydroxide aqueous solution is added dropwise for hydrolysis reaction to obtain a maleic acid aqueous solution, and the hydrolysis pH is controlled at 5-6, and then 1-3% by mass of maleic anhydride sodium tungstate or sodium molybdate is added as a catalyst, and a 27.5% by mass hydrogen peroxide aqueous solution is added dropwise for reaction, the amount of hydrogen peroxide added is (1.2-1.5) times the molar amount of maleic anhydride, the dropping temperature is controlled at 55-65°C, the dropping is completed in 2-3 hours, the temperature is kept for 1-2 hours, and the temperature is lowered to obtain an epoxysuccinic acid reaction solution; According to the recycling method of maleic anhydride epoxidation catalyst, the anion exchange column in step 1 is cylindrical, and the aspect ratio of the resin-filled part is 20-40; the anion exchange resin is required to be stable under the temperature and oxidant conditions described in step 3).
[0013] According to the recycling method of maleic anhydride epoxidation catalyst, LH-207 chloride type anion exchange resin is selected as the anion exchange column, and the amount of resin used is 3 to 10 times the mass of the catalyst.
[0014] According to the recycling method of maleic anhydride epoxidation catalyst, the amount of resin used is 3 to 5 times the mass of the catalyst.
[0015] According to the recycling method of maleic anhydride epoxidation catalyst, the catalyst in step 1) is a mixture of sodium tungstate or sodium molybdate in any proportion.
[0016] According to the recycling method of maleic anhydride epoxidation catalyst, if the total amount of the catalyst with anionic resin as carrier in step 3) is less than 1-3% of the mass of maleic anhydride, the catalyst is added to the kettle.
[0017] According to the recycling method of maleic anhydride epoxidation catalyst, in step 3), the mass ratio of maleic anhydride to water is 1:(0.5-1), and the molar ratio of maleic anhydride to hydrogen peroxide is 1:(1.2-1.5).
[0018] Beneficial effects of the present invention: The recycling method of maleic anhydride epoxidation catalyst provided by the present invention uses a specific anion resin to adsorb the catalyst in the reaction system. It only needs to add the resin adsorbing tungsten and molybdenum catalysts to the reaction system. Under the reaction temperature and pH conditions of the system, the catalyst can be almost completely automatically decomposed, avoiding the alkali washing and desorption process in the traditional adsorption method, shortening the processing cycle, and realizing multiple recycling of the catalyst and the adsorption resin. At the same time, the method of the present invention has simple operation steps, avoids the use of alkali solution, not only reduces the generation of salt and saves the amount of water, but also saves the energy consumed by external distillation of water when the catalyst is subsequently extracted, thereby reducing the production cost. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with embodiments.
[0020] The recycling method of the catalyst comprises the following steps: Step 1: First, epoxysuccinic acid is synthesized by the following method: maleic anhydride and water of equal mass are put into a kettle, and hydrolyzed with a 32% mass fraction sodium hydroxide aqueous solution to obtain a maleic acid aqueous solution, and the hydrolysis pH is controlled at (5-6), and then sodium tungstate or sodium molybdate with a mass fraction of (1-3)% maleic anhydride is added as a catalyst, and a 27.5% mass fraction hydrogen peroxide aqueous solution is added dropwise to react, and the amount of hydrogen peroxide added is (1.2-1.5) times the molar amount of maleic anhydride. The dropping temperature is controlled at 55-65°C, and the addition is completed in 2-3 hours, and the temperature is kept warm for 1-2 hours, and the temperature is lowered.
[0021] Step 2: The temperature of the synthesized epoxysuccinic acid reverse solution is lowered to 20-30°C, and all of it is passed into an anion exchange column, and the anion of the catalyst is adsorbed by the anion exchange resin. Then, the anion exchange column is eluted with pure water (1-2) times the mass of the anion exchange resin. The eluent and the adsorbed reaction solution are used for the synthesis of polyepoxysuccinic acid. After elution, the anion exchange column is disassembled, and the anion resin inside is taken out for standby use; Step 3: Add a certain amount of maleic anhydride and water to the reactor, the mass ratio of maleic anhydride to water is 1: (0.5~1), then add liquid alkali with a mass fraction of 32% to hydrolyze, stop adding liquid alkali when the pH value of the system reaches (5~6), add anionic resin adsorbed with catalyst to the reactor, heat to 55~65°C, start adding a certain amount of hydrogen peroxide aqueous solution with a mass fraction of 25%, the molar ratio of maleic anhydride to hydrogen peroxide is 1: (1.2~1.5), add it within 2~3h, keep warm for 1~2h and then cool it down, filter it after the temperature of the reaction liquid drops to 20~30°C, filter it after the temperature of the reaction liquid drops to 20~30°C, separate the resin and the reaction liquid, and treat the obtained resin and reaction liquid according to the operation described in step 1 to complete the recycling of the catalyst.
[0022] The anion exchange column used in the present invention is cylindrical, and the aspect ratio of the resin-filled part is (20-40); the anion exchange resin is required to be stable under the temperature and oxidant conditions described in step 2, preferably LH-207 chloride-type anion exchange resin, and the amount of resin used is 3-10 times the mass of the catalyst, preferably 3-5 times.
[0023] The catalyst used in the synthesis of epoxysuccinic acid is a mixture of sodium tungstate or sodium molybdate in any proportion, and the amount used is (1-3)% of the mass of the maleic anhydride. If the total amount of the catalyst with anionic resin as carrier is less than (1-3)% of the mass of maleic anhydride, the catalyst is added to the kettle.
[0024] After using anion resin to adsorb the catalyst tungstate or molybdate, in addition to soaking in alkali solution to desorb the free tungstate ions or molybdate ions, directly adding them to the epoxysuccinic acid reaction system can also desorb the tungstate ions or molybdate ions at 55~65℃. The desorption of the catalyst at 55~65℃ is carried out in the epoxysuccinic acid reaction system and shows excellent catalytic effect; simply limiting the temperature conditions cannot achieve the above effect.
[0025] The main raw material equipment specifications used in the present invention are as follows: the reaction kettle is a 2000L enamel kettle; the anion exchange resin column is 2m long and has a bottom diameter of 8cm; the resin uses LH-207 chloride-type anion exchange resin; maleic anhydride is industrial grade; hydrogen peroxide is industrial grade, with a content of 27.5%; liquid alkali is industrial grade, with a content of 32%; the catalyst uses industrial grade sodium tungstate; and pure water is produced by the company. Example
[0026] Step 1): The first synthesis step of epoxysuccinic acid, 200kg maleic anhydride and 200kg pure water are put into the kettle, stirring is started, and 32% liquid alkali by mass is added at a rate of 100kg / h for hydrolysis. When the pH value of the system reaches 5-6, the addition of liquid alkali is stopped, 4kg sodium orthotungstate is added to the kettle, stirring is continued, heating is turned on, the system temperature is controlled at 60±5°C, and 305kg hydrogen peroxide with a content of 27.5% is added at a rate of 121kg / h. After the addition is completed, the temperature is kept warm for 1h, and then cooled to room temperature to obtain 957.6kg of epoxysuccinic acid reaction solution with a content of 27.35%, and the yield is 97.23% (calculated as maleic anhydride).
[0027] Step 2): Add 12kg LH-207 chloride anion exchange resin to the anion exchange column and compact it, pass the above 957.6kg epoxysuccinic acid reaction solution into the anion exchange column for adsorption, wait for the reaction solution to pass through the anion exchange column, rinse the anion exchange column with 12kg pure water, collect the eluent and the adsorbed reaction solution and mix them for ring-opening polymerization, take out the adsorbed LH-207 chloride anion exchange resin and set aside.
[0028] Step 3): Add 200kg maleic anhydride and 100kg pure water to the reactor, start stirring, and add 32% sodium hydroxide aqueous solution to the reactor at a rate of 100kg / h for hydrolysis. When the pH value of the reaction liquid reaches 5.89, stop adding. Add the adsorbed LH-207 chloride anion exchange resin to the reactor, start heating, continue stirring, control the temperature in the reactor to 60±5℃, and start adding 305kg of 27.5% hydrogen peroxide aqueous solution at a rate of 127kg / h. Add after 3h, keep warm for 2h and then cool down. After the reaction liquid temperature drops to 30℃, filter and separate 12.5kg resin and 856.3kg reaction liquid. The obtained resin is loaded into the anion exchange column for reuse according to step 1. The reaction liquid is operated according to step 1, and the obtained mixed liquid is 880.1kg. After testing: the content of epoxysuccinic acid in the mixed solution is 29.74%, and the yield (calculated as maleic anhydride) is 97.16%; ICP detection showed that the tungsten content in the reaction solution was 2596.53 ppm, and the tungsten content in the mixed solution was 4.57 ppm.
[0029] Example 2 (Second Recycling of Resin), Step 1): Add 12.5 kg of wet LH-207 chloride anion exchange resin obtained in Example 1 to the anion exchange column and compact it, pass 956.3 kg of the reaction solution obtained in Example 1 into the anion exchange column for adsorption, wait for the reaction solution to pass through the anion exchange column, rinse the anion exchange column with 12 kg of pure water, collect the elution and the adsorbed reaction solution, mix them and use them for ring-opening polymerization, take out the adsorbed LH-207 chloride anion exchange resin and set aside.
[0030] Step 2): Add 200kg maleic anhydride and 200kg pure water to the reactor, start stirring, and add 32% sodium hydroxide aqueous solution to the reactor at a rate of 100kg / h for hydrolysis. When the pH value of the reaction liquid reaches 5.12, stop adding. Add the adsorbed LH-207 chloride anion exchange resin to the reactor, start heating, continue stirring, control the temperature in the reactor to 60±5℃, and start adding 380kg of 27.5% hydrogen peroxide aqueous solution at a rate of 152kg / h. Add after 2h, keep warm for 1h and then cool down. After the reaction liquid temperature drops to 20℃, filter and separate 12.4kg resin and 1046.3kg reaction liquid. The obtained resin is loaded into the anion exchange column for reuse according to step 1. The reaction liquid is operated according to step 1. The obtained mixed liquid is 1070.5kg. After testing: the content of epoxysuccinic acid in the mixed solution is 24.43%, and the yield (calculated as maleic anhydride) is 97.09%; ICP detection showed that the tungsten content in the reaction solution was 2130.74 ppm, and the tungsten content in the mixed solution was 4.78 ppm.
[0031] Example 3 (Multiple Recycling of Resins) The LH-207 chloride-type anion exchange resin obtained in Example 2 was further recycled under the conditions of Example 1, and still had good adsorption and catalytic capabilities after 10 cycles. The adsorption capacity was reflected by the content of catalyst tungsten element in the liquid after adsorption, and the catalytic capacity was reflected by the yield of the product epoxysuccinic acid. The test results of 0, 1, 5 and 10 cycles are shown in Table 1.
[0032] Table 1 Cycle times 0 times 1 time 5 times 10 times Yield / % 97.16 97.09 97.02 96.87 Tungsten content (adsorption liquid) / ppm 4.57 4.78 4.62 4.83 Comparative Example 717 type anion exchange resin was used to replace LH-207 chloride type anion exchange resin for reaction, and other conditions were the same as those in Example 1. The results showed that: using the resin for the first reaction, 858.9 kg of epoxysuccinic acid aqueous solution with a content of 30.47% was obtained, with a yield of 97.15%, and good catalytic performance; after the first reaction, the resin would be oxidized and destroyed by hydrogen peroxide at the reaction temperature, resulting in a sharp decrease in adsorption capacity. Under the same conditions, 870.7 kg of adsorption liquid was obtained, and the tungsten content was as high as 2184.39 ppm, indicating that the resin only adsorbed 14.69% of the catalyst anions.
[0033] From the comparison between the embodiment and the comparative example, it can be seen that the use method of the epoxysuccinic acid catalyst provided by the present invention, using a specific resin as a medium, can effectively adsorb the catalyst at low temperature and release the catalyst at the reaction temperature, thereby achieving the purpose of catalyst recycling. This process avoids the elution operation, and the resin can be recycled for multiple times, greatly reducing production costs and energy consumption.
[0034] The recycling method of maleic anhydride epoxidation catalyst provided by the present invention uses a specific anion resin to adsorb the catalyst in the reaction system. It only needs to add the resin adsorbing tungsten and molybdenum catalysts to the reaction system. Under the reaction temperature and pH conditions of the system, the catalyst can be almost completely automatically decomposed, avoiding the alkali washing and desorption process in the traditional adsorption method, shortening the processing cycle, and realizing multiple recycling of the catalyst and the adsorption resin. At the same time, the method of the present invention has simple operation steps, avoids the use of alkali solution, not only reduces the generation of salt and saves the amount of water, but also saves the energy consumed by external distillation of water when the catalyst is subsequently extracted, thereby reducing the production cost.
[0035] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for recycling maleic anhydride epoxidation catalyst, characterized in that: 1) Maleic anhydride and water are put into a reaction kettle, and a sodium hydroxide aqueous solution is added dropwise for hydrolysis reaction to obtain a maleic acid aqueous solution, and then sodium tungstate or sodium molybdate is added as a catalyst, and a hydrogen peroxide aqueous solution is added dropwise to react to obtain an epoxysuccinic acid reaction solution; 2) The temperature of the synthesized epoxysuccinic acid reaction liquid is lowered to 20-30°C, and all of it is passed into an anion exchange column, and the anion of the catalyst is adsorbed by the anion exchange resin. Then, the anion exchange column is eluted with pure water of 1-2 times the mass of the anion exchange resin. The eluent and the adsorbed reaction liquid are used for the synthesis of polyepoxysuccinic acid. After elution, the anion exchange column is disassembled, and the anion resin inside is taken out for standby use; 3) Add a certain amount of maleic anhydride and water to the reactor, then drop 32% by mass of liquid alkali for hydrolysis, stop dropping the liquid alkali when the pH value of the system reaches 5-6, add the anion resin adsorbed with the catalyst in step 2) to the reactor, raise the temperature to 55-65°C, start dropping a certain amount of 25% by mass of hydrogen peroxide aqueous solution, and complete the addition in 2-3 hours. Continue to keep the temperature for 1-2 hours and then cool down. After the temperature of the reaction liquid drops to 20-30°C, filter and separate the anion resin and the epoxysuccinic acid reaction liquid. The obtained anion resin and the epoxysuccinic acid reaction liquid are treated according to the operation described in step 2 to complete the recycling of the catalyst.
2. The method for recycling the maleic anhydride epoxidation catalyst according to claim 1, wherein: In step 1), maleic anhydride and water of equal mass are put into a kettle, and a sodium hydroxide aqueous solution with a mass fraction of 32% is added dropwise for hydrolysis reaction to obtain a maleic acid aqueous solution, and the hydrolysis pH is controlled at 5-6, and then sodium tungstate or sodium molybdate with a mass fraction of 1-3% of maleic anhydride is added as a catalyst, and a hydrogen peroxide aqueous solution with a mass fraction of 27.5% is added dropwise for reaction, and the amount of hydrogen peroxide added is (1.2-1.5) times the molar amount of maleic anhydride, and the dropping temperature is controlled at 55-65° C., and the dropping is completed in 2-3 hours, and the temperature is kept for 1-2 hours, and the temperature is lowered to obtain an epoxysuccinic acid reaction solution.
3. The recycling method of maleic anhydride epoxidation catalyst according to claim 1, characterized in that: The anion exchange column in step 1 is cylindrical, and the aspect ratio of the resin-filled part is 20-40; the anion exchange resin is required to be stable under the temperature and oxidant conditions described in step 3).
4. The method for recycling maleic anhydride epoxidation catalyst according to claim 1, characterized in that: The anion exchange column uses LH-207 chloride-type anion exchange resin, and the amount of resin used is 3 to 10 times the mass of the catalyst.
5. The method for recycling the maleic anhydride epoxidation catalyst according to claim 4, characterized in that: The amount of resin used is 3 to 5 times the mass of the catalyst.
6. The method for recycling maleic anhydride epoxidation catalyst according to claim 1, characterized in that: The catalyst in step 1) is a mixture of sodium tungstate or sodium molybdate in any proportion.
7. The method for recycling the maleic anhydride epoxidation catalyst according to claim 1, characterized in that: If the total amount of the catalyst using the anionic resin as a carrier in step 3) is less than 1-3% of the mass of maleic anhydride, the catalyst is added to the kettle.
8. The method for recycling the maleic anhydride epoxidation catalyst according to claim 1, characterized in that: In step 3), the mass ratio of maleic anhydride to water is 1:(0.5-1), and the molar ratio of maleic anhydride to hydrogen peroxide is 1:(1.2-1.5).
Citation Information
Patent Citations
Preparation method for polyepoxy sodium succinate for water treatment
CN101602852B
Production method of polyepoxysuccinic acid
CN103709387B
Preparation method of epoxysuccinic acid catalyst
CN103755945B
Poly epoxy butanedioic acid and its salt preparing method
CN1470493A
Cyclic utilization device of catalyst in epoxysuccinic acid synthesis process
CN211586523U
Cited By
Method for synthesizing epoxysuccinic acid under catalysis of titanate
CN122036652A